Perbaikan Kualitas Kayu dan Produk Mebel di Art Antique dan Mebel Kayu Jati - Sushardi, Sushardi; Woesono, Hastanto Bowo; Suwadji, Siman; Hadi, Didik Surya (Empowerment: Jurnal Pengabdian Masyarakat, 2024)
The main problem in the furniture industry is the quality of wood and furniture products due to the lack of knowledge about wood, available tools machinery, and labor. To deal with these problems, the solutions offered are counseling, training in wood and furniture products knowledge, and procurement of planer and finishing machines. The purpose of the service is to find out the quality problems of wood and furniture products in the antique art and teak wood furniture industry. Community service methods with counseling, training on the quality of wood and furniture products, and procurement of planer and finishing machines. Targets and outputs are to increase knowledge of the quality of wood and furniture products and the procurement of planners and finishing machines. The results of the service show that counseling and training on wood and furniture product knowledge is very effective for increasing knowledge of the quality of wood and furniture products. The use of planer and finishing machines can improve the quantity, quality, and innovation of products.